AMORES INCERTOS: ELENA FERRANTE E A CRÍTICA DA PERFORMATIVIDADE “FEMININA” - Fernandes, Verônica Daminelli (2019)
The main purpose of this article is to analyze the female protagonists of the book “Crônicas do Mal de Amor”, by Italian writer Elena Ferrante, as examples that illustrate the disruption of the common imagery of women that question their "natural identity." Ferrante writes her characters in constant conflict with the dominant discursive processes that are established by the repetition of socio-cultural performative acts. In addition, this paper wants to show the relevance of a literature that argues against the subjectivity of women in which being a woman still carries, in the collective imaginary what Judith Butler has refered to as "gender performativity". This work aims to illustrate how Ferrante’s writing dramatizes the "reality" and tries to subvert and put in conflict the female intelligibility, especially by conflicts related to motherhood and the need to love a man by the notion of complementary patriarchal binary that supports male superiority in the public sphere.